Mengele : unmasking the "Angel of Death" - Marwell, David G. 1951- (W.W. Norton & Company, 2020)
"A gripping account of the infamous Nazi doctor, from a former Justice Department official tasked with uncovering his fate. One of the most notorious war criminals of all time, Dr. Josef Mengele has come to symbolize both the evil of the Nazi regime and the failure of justice in the postwar world. Drawing on new scholarship and sources, historian David G. Marwell examines Mengele's life and career, chronicling his university studies, which led to two PhDs and a promising career as a scientist; his wartime service, in combat and at Auschwitz, where his "selections" determined the fate of countless innocents and his "scientific" pursuits resulted in the traumatization and death of thousands more; and his postwar refuge in Germany and South America. Mengele describes the international search in 1985, which ended in a cemetery in Sao Paulo, Brazil, and the dogged forensic investigation that produced overwhelming evidence that Mengele had died-but failed to convince those who, arguably, most wanted him dead. This is a story of science without limits, escape without freedom, and resolution without justice."--